Recurrent Implantation Failure May Be Identified by a Combination of Diagnostic Biomarkers: An Analysis of Peripheral Blood Lymphocyte Subsets - Cai, Jun-Ying; Tang, Yuan-Yuan; Deng, Xi-He; Li, Yan-Juan; Liang, Gui; Meng, Ya-Qing; Zhou, Hong (Frontiers in Endocrinology, 2022)
Background: Recurrent implantation failure (RIF) is a challenge during assisted reproductive technology (ART). In the present study, potential diagnostic biomarkers for the immune status of peripheral blood lymphocyte subsets in patients with RIF were analyzed, with the aim of identifying novel biomarkers that may predict RIF. Methods: A total of 41 participants, including 21 women with RIF and 20 fertile controls, were included in the present study. Functional analysis was performed and the cytokine status of natural killer (NK), T, CD8+ T, T helper (Th), γδ T cells which are lymphocyte subsets in peripheral blood was measured using flow cytometry. Binary logistic regression analysis adjusted for T follicular helper 1 (Tfh1), Tfh2, Tfh17 and early NK cells was performed to determine the relationship between the peripheral blood lymphocyte subsets and RIF. Potential diagnostic biomarkers were assessed by logistic regression analysis and receiver operating characteristic curves. Results: There were significantly more Tfh1, Tfh17 and NK cells in the RIF group compared with the control group (all P<0.05). However, the percentage of T, regulatory T (Tregs) and Tfh2 cells, as well as early inhibitory NK cells, were significantly lower in the RIF group compared with the control group (all P<0.05). Following logistics regression analysis, Treg, Tfh17 and early inhibitory NK cells exhibited significant differences between the two groups. Combination diagnosis using these 3 biomarkers had a higher area under the curve of 0.900 (95% confidence interval: 0.808-0.992, P<0.001) in the RIF group compared with that in the control group. Conclusions：T, Tregs, Tfh1, Tfh2, Tfh17, NK cells and early inhibitory NK cells may play important regulatory roles in embryo implantation. The combination of 3 molecular markers (Treg, Tfh17 and early inhibitory NK cells) could provide a high diagnostic value for women with RIF, thus providing novel potential biomarkers for RIF in ART. The present findings could provide a reference either for the clinical treatment of patients with RIF or for future large, well-designed studies.